Prognosticators and Risk Grouping in Patients with Lung Metastasis from Nasopharyngeal Carcinoma: A more accurate and appropriate assessment of prognosis - Cao, Xun (BioMed Central, 2011)
BACKGROUND: Lung metastases arising from nasopharyngeal carcinomas (NPC) have a relatively favourable prognosis. The purpose of this study was to identify the prognostic factors and to establish a risk grouping in patients with lung metastases from NPC. METHODS: A total of 198 patients who developed lung metastases from NPC after primary therapy were retrospectively recruited from January 1982 to December 2000. Univariate and multivariate analyses of clinical variables were performed using Cox proportional hazards regression models. Actuarial survival rates were plotted against time using the Kaplan-Meier method, and log-rank testing was used to compare the differences between the curves. RESULTS: The median overall survival (OS) period and the lung metastasis survival (LMS) period were 51.5 and 20.9 months, respectively. After univariate and multivariate analyses of the clinical variables, age, T classification, N classification, site of metastases, secondary metastases and disease-free interval (DFI) correlated with OS, whereas age, VCA-IgA titre, number of metastases and secondary metastases were related to LMS. The prognoses of the low- (score 0-1), intermediate- (score 2-3) and high-risk (score 4-8) subsets based on these factors were significantly different. The 3-, 5- and 10-year survival rates of the low-, intermediate- and high-risk subsets, respectively (P < 0.001) were as follows: 77.3%, 60% and 59%; 52.3%, 30% and 27.8%; and 20.5%, 7% and 0%. CONCLUSIONS: In this study, clinical variables provided prognostic indicators of survival in NPC patients with lung metastases. Risk subsets would help in a more accurate assessment of a patient's prognosis in the clinical setting and could facilitate the establishment of patient-tailored medical strategies and supports.